Evaluation of Antioxidant Supplementation on Redox Unbalance in Hyperthyroid Cats Treated with Methimazole: A Blinded Randomized Controlled Trial - Alessia Candellone; Paola Badino; Paola Gianella; Flavia Girolami; Graziella Raviri; Vittorio Saettone; Giorgia Meineri (MDPI AG, 2019)
Methimazole (MMI) is often the selected medical treatment for feline hyperthyroidism. However, the onset of MMI-related side effects (MMI-SE) is likely caused by oxidative stress. This study evaluated the dietary supplementation of selected antioxidants in hyperthyroid cats receiving MMI, to reduce MMI-SE. Thirty hyperthyroid client-owned cats were randomly allocated in group M (MMI + placebo) or group M+A (MMI + antioxidants). At different time-points from the enrolment (ET) to the end of the trial (FT), the following information was recorded: clinical findings, complete blood count, serum biochemical parameters, urinalysis, total plasma thyroxine concentrations, determinable reactive oxygen metabolites (dROMs), OXY-adsorbent test values, and oxidative stress index (OSi) values, and MMI-SE. dROMs and OSi values significantly increased from ET to FT in group M and were significantly higher in group M than in group M+A at FT. Likewise, OXY-absorbent test values were significantly higher in group M+A than in group M at FT. Moreover, the occurrence rate of MMI-SE in group M+A was lower than in group M. In conclusion, our results show that the dietary supplementation of antioxidants in hyperthyroid cats receiving MMI exerts a protective effect against oxidative stress, likely contributing to the reduction of MMI-SE.